Pengaruh Self Efficacy dan Work Engagement terhadap Employee Performance melalui Job Satisfaction pada Karyawan PT. X. - Naufan Dhani Ramadhan; Budiono Budiono (Jurnal Ilmu Manajemen, 2023)
This study aims to test and analyse the effect of self efficacy and work engagement on employee performance through job satisfaction in employees of PT X. This research uses quantitative testing methods with the number of respondents as many as 67 production employees with sampling techniques, namely saturated sampling techniques to collect data from production employees at PT X. SEM-PLS analysis technique was used in this study with the help of SmartPLS 3.0 software. The results obtained from this study indicate that self efficacy has a significant positive effect on employee performance. self efficacy has a significant positive effect on job satisfaction. work engagement has a significant positive effect on employee performance. work engagement has a significant positive effect on job satisfaction. job satisfaction has a significant positive effect on employee performance. job satisfaction does not mediate the effect between self efficacy on employee performance. job satisfcation mediates the influence between work engagement on employee performance. implications based on the results described in this study indicate that companies need the role of superiors to always provide a form of support to employees in the form of motivation and by always creating a good environment and being fair to each employee.